Detection and quantification of rituximab in the human urine - Jacobs, Roland; Langer-Jacobus, Thais; Duong, Michelle; Stahl, Klaus; Haller, Hermann; Schmidt, Reinhold E.; Schiffer, Mario (Journal of Immunological Methods, 2017)
B cell depletion by rituximab treatment might be inefficient in patients suffering from nephrotic syndrome. Due to the impaired glomerular filtration barrier a significant portion of the therapeutic antibody might be lost into the urinary space. In order to determine the amount of rituximab in the urine of such patients, CD20+ Daudi cells were stained with the patients' urine followed by a fluorochrome-labeled secondary antibody. Mean fluorescence intensity of that way labeled Daudi cells was determined by flow cytometry. Control samples with defined rituximab concentrations were used to create standard curves. The analyses revealed that all nephelometric IgG+ urine samples tested also manifested rituximab at concentrations between 100 and 46,707μg/L. The flow cytometry-based approach is an easy and reliable method to assess rituximab in patients' urine samples for monitoring individual rituximab treatment courses in all patients co-presenting impaired renal filtration. Presence of such antibodies in the urine could be considered as criteria to modify the formulation or modality of rituximab delivery in order to prevent the loss of the therapeutic antibodies and thereby ensuring efficacy of the therapy.
EVALuna2:34544